Dead boy detectives. Vol. 2, Ghost snow - Litt, Toby, 1968- (DC Comics/Vertigo, 2015)
"From the pages of THE SANDMAN, Neil Gaiman's intrepid dead schoolboys head back to the horror that is St. Hilarions School--the place where they both were murdered. Written by Toby Litt and illustrated by Mark Buckingham (FABLES) DEAD BOY DETECTIVES VOL. 2 features the second mysterious arc from the new hit series from Vertigo. Collects DEAD BOY DETECTIVES #7-12"--